2010
DOI: 10.2332/allergolint.09-oa-0107
|View full text |Cite
|
Sign up to set email alerts
|

Rush Specific Oral Tolerance Induction in School-Age Children with Severe Egg Allergy: One Year Follow Up

Abstract: Our rush SOTI is a safe and effective treatment for severe food allergy since only a few weeks are needed to acquire tolerance. It would replace allergen avoidance as the treatment for food allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 34 publications
6
74
2
2
Order By: Relevance
“…The maximum dose of OM in this OIT protocol was 0.151 g OM/kg of body weight (5.0 mg OM/mouse, mouse body weight 33 g). This amount is approximately the same as that used in human OIT (15). Thus, the result of the OIT protocol shows that the present OIT protocol may be applicable OIT for humans allergic to eggs.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The maximum dose of OM in this OIT protocol was 0.151 g OM/kg of body weight (5.0 mg OM/mouse, mouse body weight 33 g). This amount is approximately the same as that used in human OIT (15). Thus, the result of the OIT protocol shows that the present OIT protocol may be applicable OIT for humans allergic to eggs.…”
Section: Discussionsupporting
confidence: 54%
“…It has been reported that rush OIT improved allergic responses in human patients (14,15). Itoh et al used rush OIT for severe allergy as a therapeutic treatment (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies of egg OIT included the small RCTs by Dello Iacono et al and Meglio et al, who reported desensitization rates of 80%-90% in children with severe egg allergy, and 2 studies using rush protocols with desensitization induced in as few as 5 days [32][33][34][35].…”
Section: Egg Oitmentioning
confidence: 99%
“…A similar approach has also been used for hen's egg allergy. 20,22 Another approach to decrease the logistical burden of OIT has been to have subjects increase doses at home following an in-hospital rush protocol for milk allergy. 49 In this study, patients were given instructions on how to increase their doses and on how to treat specific symptoms with specific medications; notably, patients were instructed to use nebulized epinephrine followed by β-2 agonist for cough, wheeze, tightness of chest, or change in voice.…”
Section: Increasing Desensitization Efficacymentioning
confidence: 99%